Testicular zinc, copper and iron concentrations in male rats exposed to subacute and subchronic formaldehyde gas inhalation - Ozen, OA; Yaman, M; Sarsilmaz, M; Songur, A; Kus, I (Elsevier Gmbh, Urban & Fischer Verlag, 2002)
The level of trace elements such as Zn, Cu and Fe in testicular tissue is an indication of the condition of the tissue as these elements take over important tasks. Zinc and copper are the prosthetic groups of several metalloenzymes including superoxide dismutase (SOD) which is an important antioxidant enzyme in the cellular protection from reactive oxygen species. If concentrations of these trace elements decrease significantly, SOD cannot detoxify harmful oxygen species. In this study, adult mate rats (wistar-albino) were exposed to formaldehyde at different periods (subacute and subchronic) and concentrations (0; 12.2; 24.4 mg . L(-1)). Body and testis weights were recorded and compared with control groups. The metals described above were determined in rat testicular tissue by atomic absorption spectrometry by using wet ashing. We conclude that subacute or subchronic exposure to formaldehyde have caused growth retardation and altered levels of trace elements, including copper, zinc and iron, in testicular tissue, and may induce further oxidative damage on testicular tissue Leading to spermatozoal abnormalities.
Keywords: formaldehyde toxicity; inhalation; zinc; copper; iron; subacute; subchronic